ICT and basic competences (Journal of Parents and Teachers, 2016)
The following article deals with the relationship between ICT and the basic competences. In this case, it refers to the personal autonomy and initiative which is based on activities to work together the new technologies and the student’s autonomy capacity development.
Keywords: education; competence; autonomy; ICT; activities; capacity.